Improving Creative Thinking Ability and Achievement with Problem-Based Learning in Science Subjects - Nasukha, Muhyani; Fitriyah, Nusaibah; Sutisna, Sutisna (Cakrawala: Jurnal Pendidikan, 2022)
This study aims to determine the effect of the application of the Problem based learning model in an effort to improve creative thinking skills and student achievement at PIONEER Depok Elementary School in science subjects. One of the advantages of the Problem-based learning model is that it is able to train students to think high-level, critically and creatively in solving problems. Creative thinking ability can be measured based on indicators of fluency, flexibility of originality in thinking, and thinking in detail. The research method used is quasi-experimental. The results obtained must be from the learning is that there is a significant influence in the application of the PBL (Problem Based Learning) model on student achievement. This means that the implementation of Problem Based Learning is effective in increasing students' creative thinking skills and learning achievement. This research was conducted by observing and doing pre-test and post-test to show maximum results so that the implementation of PBL in science learning.